Effect of oxidation time on microstructure and electromagnetic properties of FeSiAl alloy powders - GUO Yang; BI Lei (Fenmo yejin jishu)
The effect of oxidation time on the microstructure and electromagnetic properties of the FeSiAl alloy powders was investigated at 500 ℃ in air, using FeSiAl alloy powders as the raw materials. The results show that, the surface color of the FeSiAl alloy powders changes from gray to yellow with the increase of oxidation time, and there is no significant change of the surface microstructure. After the oxidation time reaches 5 h, Fe3O4 can be found and gradually transforms into Fe2O3 as the oxidation time up to 10 h. The surface oxide layer of the FeSiAl alloy powders is mainly composed of Fe2O3, SiO2, and Al2O3. The real part of the permittivity and permeability of the powders show an upward trend with the oxidation time increasing, and there is no obvious change in the imaginary part of the permittivity and permeability.